Modal analysis of ball bearings using finite element method - Bojanić Šejat, Mirjana; Rackov, Milan; Knežević, Ivan; Živković, Aleksandar (Journal of Production Engineering, 2022)
Dynamic behavior of roller bearings under the loads can be described by a mathematical model. The dynamic bearing model is modeled using the finite element method. Analysis of the dynamic behavior of the radial bearing refers to the modal analysis, ie. the determination of the natural frequencies, the main forms of oscillation and damping for the considered bearing, with different values of the clearance. This analysis is based on the simultaneous analysis of excitation and response signals in the time domain or more often in the frequency domain. In addition to FEM, it was also performed the experimental test on a FKL 6006 bearing with different clearance values. Within this paper, a comparison of the results of the modal analysis performed experimentally with the results obtained by the finite element method was performed. The compared results show a satisfactory deviation.